Aksi Perbaikan Mutu Sekolah terhadap Kedisiplinan Siswa melalui Pelaksanaan Tata Tertib di SMP Ma’arif 1 Kebumen - Wiwit Nurhidayati; Adyanil Afiyyah; Sarwiati Sarwiati; Nurroniyah Fatimatul; Sukron Hidayat (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2022)
Improving the quality of schools must always be carried out continuously in order to achieve educational goals. However, schools often ignore the little things that actually really support efforts to improve school quality, such as school rules. This study aims to find problems related to school quality improvement, determine quality improvement work priorities, carry out school quality improvement action activities, and reflect on the importance of school quality improvement through action. Location of activities at SMP Ma’arif 1 Kebumen. The management theory used is the plan-do-check-act (PDCA) model. Data collection techniques were through problem mapping, determining work priorities, implementing actions, and reflecting, which were carried out with partners in a participatory manner with the Deputy Head of Student Affairs, the Student Council Teacher, and the Student Council of Middle School Maarif 1 Kebumen. The results were (a) a number of problems related to school quality were found, (b) disciplinary work priorities were determined through the implementation of school rules, (c) socialization was held with action partners, (d) actions were held in the form of controlling school rules and student discipline, (e the reflection is that the partners realize the importance of school rules and at the same time their implementation is carried out together.